Thermo-Mechanical and Wear Properties of Natural Fiber-Reinforced Epoxy Composites for Structural Applications - Mayank Bharadvaj; Jitendra Yadav; Brijesh Gangil (Mechanics of Advanced Composite Structures)
Grewia Optiva fiber-based polymer composites were prepared with the addition of Marble dust (MD) in varying percentages by hand-layup technique. To understand the behavior of the material, a detailed physical, mechanical, and thermo-mechanical analysis of the samples was conducted. The findings reveal that the addition of MD to 10 wt. % helps in enhancing the interfacial bonding between the fiber and epoxy. Due to the high void fraction and poor surface interaction, further addition of MD restricts beneficial changes in the composite. The thermo-mechanical analysis (DMA) illustrates that adding marble dust powder results in a decrease in chain mobility, hence enhancing the storage modulus of all samples. Due to its maximum elastic and low viscous regions, the GM-2 (MD 10 wt. %) specimen exhibits the lowest level of energy dissipation. The research also focuses on the sliding wear behavior of the material, and a Taguchi design approach is also used for parametric analysis of wear response. In conclusion, the Grewia Optiva fiber polymer composite with (GM-2) 10 wt.% marble dust shows the best mechanical, thermo-mechanical, and sliding wear results due to its superior interfacial bonding and can be found suitable for fabrication of portable cabins.